PENYUSUNAN SOFTWARE PREDIKSI KEBUTUHAN RUNWAY, TAXIWAY, APRON DAN TERMINAL PENUMPANG - , ALIDINA NURUL HIDAYAH ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Nowadays, airport is taking important role in transportation sector. The rapid development of air transportation must be balanced with the development of airport so that the aim of transportation can be fulfilled. In planning, designing and developing of airport facilities for airside (runway, taxiway, and apron) and land side (passenger terminal), required a lot of tables and formulas. Because of that, an error would be occurred in analysis process with manual method. The computer programming for software prediction of the needs of runway, taxiway, apron and passenger terminal, can be used as a solution for fast, precise and accurate in analysis process. The analysis process on airside facilities (runway, taxiway and apron) are based on ICAO (1999) and for landside facility (terminal passenger) is based on a combination of some guidelines such as SKEP/347/XII/99, JICA (1992) and IATA (1989). The programming software that be used in this research is Visual Basic 2010 based on Windows. The data which be used to test the program validation is secondary data which taken from previous researchs. For airside and landside facilities, secondary data was taken from the final project by Zulaekhah and Setyana (2010) with Ngurah Rai Airport, Bali as study case. The result of validation test from the comparison between the manual analysis and by using the program of AirFuLs 1.0 on airport facilities such as runway, taxiway, apron and terminal passenger are 0.000%. It means that program of AirFuLs 1.0 is valid and proper to be used.